Cutting Forces in the Milling of Difficult-to-Machine Material used in the Aero Space Industry Using a Monolithic Ceramic Milling Cutter - Slabejová, Silvia; Holubjak, Jozef; Timko, Pavol; Richtárik, Michal; Krajčoviech, Stanislav; Prokein, Denis (Manufacturing Technology Journal, 2022)
The constantly developing aerospace industry places demands on increasing productivity and produc-tion efficiency. At present, new construction materials are being produced that have better physical and mechanical properties than conventional materials. In addition to new materials, new cutting materials and new machining technologies are being developed. The combination of suitable machin-ing technology, material and tool will achieve excellent product surface quality, long tool life and thus production efficiency. Due to its mechanical and physical properties, technical ceramics can be used in the machining of difficult-to-machine materials, in which there is mechanical stress on blows, impacts, abrasions and other damage. Thanks to these properties, ceramics as a material is very suit-able for the production of machine tools. The presented article deals with the applicability of ceramic milling cutters in high-speed machining of nickel alloy, which is used mainly in the aerospace indus-try. The evaluation of the experiment took place by means of DoE - analysis of cutting forces, the result of which is the creation of the dependence of cutting forces on cutting conditions. Based on the data obtained, it is possible to continue to further intensify the cutting conditions in the area of high-speed machining.
Keywords: Trochoidal Milling; Surface Quality; Monolithic Ceramic Cutter